Acute Kidney Injury and Electrolyte Imbalances Caused by Dapagliflozin Short-Term Use - António Cabral Lopes; Olga Lourenço; Sandra Morgado; Andreia Gaspar; Idalina Freire; Inês Eusébio; João Ribeiro; Mafalda Silva; Marta Mendes; Olímpia Fonseca; Rute Duarte; Manuel Morgado (MDPI AG, 2024)
Dapagliflozin, a sodium-glucose cotransporter 2 inhibitor (SGLT2i), has shown demonstrated benefits for renal and cardiovascular outcomes in large clinical trials. However, short-term concerns regarding its impact on renal function and electrolyte balance exist. This study aimed to evaluate the short-term effects of dapagliflozin on renal function and electrolyte balance in patients newly prescribed the medication. A retrospective analysis of 246 patients who initiated dapagliflozin therapy was conducted. Serum creatinine, sodium, and potassium levels were measured at baseline (before dapagliflozin) and 5-8 days after initiation (endpoint). A Wilcoxon signed-rank test, Pearson's chi-square test, and Fischer's exact test were used for the data analysis. Glycemia and sodium levels were significantly higher at the baseline compared to the endpoint (p < 0.001). Conversely, creatinine and potassium levels were significantly higher at the endpoint than at the baseline (p < 0.001). The prevalence of hyponatremia and hyperkalemia were increased at the endpoint (17.5% vs. 10.2% and 16.7% vs. 8.9%, respectively). Although not statistically significant, a trend towards increased hyponatremia with the co-administration of furosemide was observed (p = 0.089). No significant association was found between potassium-sparing medications (p > 0.05) and hyperkalemia, except for angiotensin receptor blockers (p = 0.017). The combination of dapagliflozin and furosemide significantly increased the risk of acute kidney injury (AKI) at the endpoint (p = 0.006). Age, gender, and chronic kidney disease status did not significantly influence the occurrence of AKI, hyponatremia, or hyperkalemia (p > 0.05). These findings emphasize the importance of the close monitoring of renal function and electrolyte balance, particularly in the early stages of dapagliflozin therapy, especially in patients receiving diuretics or renin-angiotensin-aldosterone system inhibitors.